2012
DOI: 10.1113/expphysiol.2012.067603
|View full text |Cite
|
Sign up to set email alerts
|

Altering the rest interval during high‐intensity interval training does not affect muscle or performance adaptations

Abstract: New Findings r What is the central question of this study?Are exercise-induced changes in metabolites and ions a crucial factor in the adaptation of contracting muscle? This was assessed by manipulating the rest period between high-intensity intervals. r What is the main finding and its importance?Our results suggest that the perturbation of muscle metabolites (specifically phophocreatine, lactate and H + ) during high-intensity interval training is not a crucial factor regulating related adaptations of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 41 publications
4
35
3
Order By: Relevance
“…Previous data (16) revealed no differences in adaptations to interval training whether recovery between bouts was relatively brief or prolonged, so the dissimilar recovery duration seems to elicit minimal effects on our findings. Sessions began with a 4-minute warm-up at 40 W followed by 6-10 bouts of HIIT.…”
Section: Baseline Testingcontrasting
confidence: 68%
See 2 more Smart Citations
“…Previous data (16) revealed no differences in adaptations to interval training whether recovery between bouts was relatively brief or prolonged, so the dissimilar recovery duration seems to elicit minimal effects on our findings. Sessions began with a 4-minute warm-up at 40 W followed by 6-10 bouts of HIIT.…”
Section: Baseline Testingcontrasting
confidence: 68%
“…In contrast, many studies have examined changes in these variables during acute exercise including HIT. One study (6) revealed significant increases in RPE ( 14), peaking at values equal to 7.0 (very hard) in response to Wingate-based SIT, similar to values equal to 16-18 on the 15-point Borg scale (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)23) in response to treadmill interval training (47). In a recent study, Oliveira et al (39) required healthy men to perform treadmill exercise at 72%V _ O 2 max and interval training at 100%V _ O 2 max which were matched for average intensity and duration.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…This was in part because the recovery phase of the interval training (3 minutes) was quite long. It may be possible to shorten the rest interval without any loss in fitness [30]. Another feature of the overall study design, incorporated to reflect best practice, was a warm up and cool down period totaling 15 minutes per exercise session.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the consequences, maximal oxygen consumption, and training effects were not different with either a short or longer rest period during interval training (Edge et al. 2013). Whether the metabolic fluctuations per se could activate in itself the signaling cascades leading to PGC-1 α is unknown.…”
Section: Introductionmentioning
confidence: 99%